Systemic Oxidative Balance Reflects the Liver Disease Progression Status for Primary Biliary Cholangitis (Pbc): The Narcissus Fountain - Marcello Dallio; Mario Romeo; Marina Cipullo; Lorenzo Ventriglia; Flavia Scognamiglio; Paolo Vaia; Giorgia Iadanza; Annachiara Coppola; Alessandro Federico (MDPI AG, 2024)
Biological antioxidant potential (BAP) and Reactive Oxygen Metabolites (dROMs) are two tests complementarily assessing systemic oxidative statuses (SOSs) that are never applied in chronic liver disorders (CLDs). We enrolled 41 ursodeoxycholic acid (UDCA)-naïve Primary Biliary Cholangitis (PBC) patients [age: 58.61 ± 11.26 years; females (F): 39], 40 patients with metabolic-dysfunction-associated steatotic livers (age: 54.30 ± 11.21; F: 20), 52 patients with HBV (age: 52.40 ± 8.22; F: 34), 50 patients with (age: 56.44 ± 7.79, F: 29), and 10 controls (age: 52.50 ± 9.64; F: 7). Liver fibrosis and the steatosis severity were determined using transient elastography, and the SOS was balanced using d-ROMs and the BAP test. The gene expressions of superoxide dismutase (SOD1; SOD2) and glutathione peroxidase (GPx1) were evaluated using real-time PCR in advanced fibrosis (AF: F3F4) in patients with PBC. In contrast to other CLDs, in PBC the dROMs and BAP levels were, respectively, directly and inversely correlated with hepatic fibrosis (dROMs, R: 0.883; BAP, R: −0.882) and steatosis (dROMs, R: 0.954; BAP, R: −0931) severity (p < 0.0001 all). Patients with PBC also revealed a progressively increasing trend of d-ROMs (F0-F2 vs. F3: p = 0.0008; F3 vs. F4: p = 0.04) and reduction in BAP levels (F0-F2 vs. F3: p = 0.0007; F3 vs. F4 p = 0.04) according to the worsening of liver fibrosis. In AF-PBC, the SOD1, SOD2, and GPx1 expressions were significantly downregulated in patients presenting SOS imbalance (SOD1, p = 0.02; SOD2, p = 0.03; GPx1, p = 0.02). SOS disequilibrium represents a leitmotiv in patients with PBC, perfectly reflecting their liver disease progression status.